New names for New Zealand weeds - Champion, P.D.; James, T.K.; Dawson, M.I. (New Zealand Plant Protection, 2010)
There have been numerous changes in botanical names of New Zealand weeds and their assignment to plant families since the publication of the relevant Flora of New Zealand volumes This paper outlines the reasons behind the changes in nomenclature including the recent use of DNA sequencing to classify plants by the Angiosperm Phylogeny Group (APG) Currently accepted name changes and new assignment of families for weeds in New Zealand are listed